Rancangan Aplikasi Customer Relationship Management pada UKM (Studi Kasus CV. AlBarru) - Leni Nurhayati (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
One effort to maintain customers and create loyal customers is to manage customer relationships using the concept of Customer Relationship Management (CRM). The application of CRM allows companies to get all customer’s information so that it will be easier in creating programs that may attract and retain customers or even create customer loyalty. Information and Communication Technology can support the implementation of CRM. CRM has been implemented by many large companies but rarely applied by small and medium enterprises (SMEs). The high level of business competition, changes in consumer behavior, and the diverse of consumer’s needs and desires make CV. AlBarru which is an SME engaged in construction to participate in implementing CRM. The purpose of this study is to identify the business processes that related to customers and to design a basic CRM system model which is then followed by making a CRM application design on CV. AlBarru. The research method used is qualitative research with the type of descriptive research and action. Descriptive research is done to describe the business processes that exist in the CV. AlBarru so that it can be adapted to the CRM concept that will be applied. Action research is done by making a CRM application design consisting of designing the process using UML and Interface design. This research produced a CRM application design that provides an overview of User needs and required processes to be made and recommendations for CRM programs that can be implemented